Box and Cox play. - Johnson, Wendell J. (collector):::Creator::::::::::::
Written on verso: ""First" production at San Jose State College-probably 1902. This may have been "Box and Cox". Picture presented by Mr. J. Wendell Johnson of the Speech and Drama Department. April, 1964."